1989
DOI: 10.1002/1097-0142(19890201)63:3<583::aid-cncr2820630331>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Expanded role for fine needle aspiration of the prostate. A study of 335 specimens

Abstract: In 279 patients, 335 cytologic samples were obtained from the prostate and correlated with histology obtained by core needle biopsy in 189 cases. Approximately 6% of the cytologic specimens were inadequate for diagnosis. The unconfirmed positive rate for malignancy was 1.6%, the false-negative rate was 27.9%, and the accuracy rate was 89.6%. Granulomatous inflammation was diagnosed in 19 cases, and three cases of tumors other than acinar carcinoma of the prostate were encountered. Based on our experience, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…According to The John Hopkins Experience, only 55% patients who met the criteria for RP had tumors that were organ confined, and in approximately 10% of cases the disease involved regional lymph nodes or seminal vesicles. 97 Correlation of cytological grading with the Gleason score has been published elsewhere 59,63,67,70,72,[77][78] and the accuracy of digitally guided transrectal FNA has been tested in comparative studies with thick and ultrasound-guided thinneedle core biopsies; both methods have equal sensitivity and specificity, and false positives are rare to nonexistent: 7,8,[15][16]27,30,[32][33]36,[55][56]59,[61][62][68][69]71,73,76,92,93,95 FNA passed this scrutiny with honors and was deemed suitable to perform a confident diagnosis of prostate cancer. According to Tannenbaum,78 when an appropriate number of samples are obtained from palpable abnormal prostates, the detection rate for cancer is the same for both aspiration and core biopsies.…”
mentioning
confidence: 99%
“…According to The John Hopkins Experience, only 55% patients who met the criteria for RP had tumors that were organ confined, and in approximately 10% of cases the disease involved regional lymph nodes or seminal vesicles. 97 Correlation of cytological grading with the Gleason score has been published elsewhere 59,63,67,70,72,[77][78] and the accuracy of digitally guided transrectal FNA has been tested in comparative studies with thick and ultrasound-guided thinneedle core biopsies; both methods have equal sensitivity and specificity, and false positives are rare to nonexistent: 7,8,[15][16]27,30,[32][33]36,[55][56]59,[61][62][68][69]71,73,76,92,93,95 FNA passed this scrutiny with honors and was deemed suitable to perform a confident diagnosis of prostate cancer. According to Tannenbaum,78 when an appropriate number of samples are obtained from palpable abnormal prostates, the detection rate for cancer is the same for both aspiration and core biopsies.…”
mentioning
confidence: 99%
“…172 The rate of inadequate sampling, although often unreported, ranges from 0.2% to 33% for aspiration biopsy. 171,[173][174][175]177,179,[181][182][183] Reported rates of inadequate core biopsy specimens range from 0% to 11%. 174,175 Carter and colleagues reported that of the 94 prostatic aspirations that could be given a definite cytological diagnosis there was eventual histological correlation in 85 (90.4%).…”
Section: Interpretation Of Biopsy Resultsmentioning
confidence: 99%
“…Higher levels of false-negative results have been reported (27.9%) when performed by trainees with varying degrees of experience and skill. 179…”
Section: Interpretation Of Biopsy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with routine Swedish practice, the standard diagnostic method since the 1960s has been fine-needle aspiration biopsy cytology (FNAB), as described by FranzCn et al (14), via the transrectal route. The complication rate is extremely low and the method is cheap and easy to use in moderately experienced hands (10,25,37). The advent of 0.9 and 1.2 mm core biopsy needles for transrectal use with spring-loaded biopsy guns (24) has led to widespread employment of this method, especially with the help of transrectal ultrasound guidance (23).…”
mentioning
confidence: 99%